2012
DOI: 10.1111/j.1526-4637.2012.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Occipital Nerve Pulsed Radiofrequency Treatment: A Multi-Center Study Evaluating Predictors of Outcome

Abstract: PRF may provide intermediate-term benefit in ON to a significant proportion of refractory cases. Careful attention to selection criteria and treatment parameters may further improve treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 39 publications
2
75
0
1
Order By: Relevance
“…Similarly, no differences for cervical and lumbar facet RF denervation outcomes have been noted when 50 and 80% cutoff thresholds were compared [91,98]. The results for RF denervation are consistent with other treatments that have found no differences in outcomes between using 50% thresholds for screening procedures and more stringent reference standards (Table 6) [99,100].…”
Section: Patient Selectionsupporting
confidence: 70%
“…Similarly, no differences for cervical and lumbar facet RF denervation outcomes have been noted when 50 and 80% cutoff thresholds were compared [91,98]. The results for RF denervation are consistent with other treatments that have found no differences in outcomes between using 50% thresholds for screening procedures and more stringent reference standards (Table 6) [99,100].…”
Section: Patient Selectionsupporting
confidence: 70%
“…117,118 Although the results from most of the reported case series and studies are favorable, there is currently little convincing evidence for the efficacy of GON blockade in the acute or preventive treatment of headache, as most data on this topic come from noncontrolled studies. Pulsed radiofrequency ablation [119][120][121][122] and botulinum toxin injection 123 to the occipital nerves have been reported in the recent literature and have shown to provide potential long-term relief for patients with occipital neuralgia. Further studies are needed to determine the role of GON block in headache disorders.…”
Section: Occipital Nerve Blocksmentioning
confidence: 97%
“…Only 3 studies 17,20,34 of the 6 studies described use of prognostic nerve blocks prior to ablative (conventional or cooled) RF treatments. Studies by Choi et al 17 and Protzman et al 34 used relatively high volumes of local anesthetic (2 mL), which have been shown to undermine the specificity of diagnostic and prognostic injections, 44 and spread to an area of tissue exponentially larger than the lesions created using 22-gauge electrodes heated at 70°C for 90 seconds. Higher volumes were also associated with poorer treatment outcomes in a study to determine factors associated with treatment success for pulsed RF of the occipital nerves.…”
Section: Prognostic Nerve Blocks To Predict Response To Ablative Rf Tmentioning
confidence: 99%
“…Higher volumes were also associated with poorer treatment outcomes in a study to determine factors associated with treatment success for pulsed RF of the occipital nerves. 44 The mechanistic basis of this phenomenon (suppression of C-fiber afferent activity) has also been elucidated. 45 In addition, Choi and colleagues' decision to require 24 hours of pain relief after a single block with lidocaine 17 is inconsistent with the pharmacodynamics of the drug.…”
Section: Prognostic Nerve Blocks To Predict Response To Ablative Rf Tmentioning
confidence: 99%